Diagnosis Kondisi Transformator Berbasis Analisis Gas Terlarut Menggunakan Metode Sistem Pakar Fuzzy - Gatut Yulisusianto; Hadi Suyono; Rini Nurhasanah (Fakultas Teknik, Universitas Brawijaya, 2015)
Dissolved gas analysis of transformer oil is one of the most effective ways to determine the transformer condition. Currently, there are many interpretation techniques that have been used in data processing of dissolved gas analysis results. However, all of the techniques used are rely based on the experience of experts who have conducted research by using the results of dissolved gas analysis. The combination of expert system and fuzzy to diagnose the dissolved gas analysis data to identify the condition of the transformer is discussed in this paper. The data used for this research is collected from several different transformers and then interpreted by using a standard methods and fuzzy expert systems, and the results are compared. From several experiments show that fuzzy expert system is more effective to identify a transformer failure.Keyword—DGA, Dissolved Gas Analysis, Fuzzy Expert System, TDCG.